2014
DOI: 10.1007/s00424-014-1603-2
|View full text |Cite
|
Sign up to set email alerts
|

Two helices in the third intracellular loop determine anoctamin 1 (TMEM16A) activation by calcium

Abstract: Anoctamin 1 (ANO1)/TMEM16A is a Cl− channel activated by intracellular Ca2+ mediating numerous physiological functions. However, little is known of the ANO1 activation mechanism by Ca2+. Here, we demonstrate that two helices, “reference” and “Ca2+ sensor” helices in the third intracellular loop face each other with opposite charges. The two helices interact directly in a Ca2+-dependent manner. Positively and negatively charged residues in the two helices are essential for Ca2+-dependent activation because neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…The role of CaM in Ano1 activation is still highly debated. Some studies have suggested that CaM directly binds Ano1 and plays a role in Ano1 activation (18,35). On the other hand, other studies found no requirement for CaM in Ano1 activation by Ca 2ϩ in cells (39) and when reconstituted in purified bilayers (35) and therefore suggest that Ca 2ϩ directly activates Ano1.…”
Section: Discussionmentioning
confidence: 99%
“…The role of CaM in Ano1 activation is still highly debated. Some studies have suggested that CaM directly binds Ano1 and plays a role in Ano1 activation (18,35). On the other hand, other studies found no requirement for CaM in Ano1 activation by Ca 2ϩ in cells (39) and when reconstituted in purified bilayers (35) and therefore suggest that Ca 2ϩ directly activates Ano1.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids 444 EEEE are important for intrinsic voltage dependence, but mutating these residues has no effect on Ca 2+ sensitivity ( 7 ). Moreover, Lee and colleagues suggested that two helices in the third intracellular loop could be structurally changed in a Ca 2+ -dependent push-and-pull fashion, like a Ca 2+ sensor ( 9 ). Because Ca 2+ is a positively-charged ion, Tien and colleagues performed systematic mutagenesis of all conserved acidic residues in ANO1 ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Y. D. Yang et al (2008) observed that the TMEM16A current activated in HEK cells coexpressing endothelin receptor subtype A was strongly outwardly rectifying, they also observed the Ca 2+ sensitivity of TMEM16A. Lee et al (2015) discovered that mutations ( 659 KMKK/ GMGG 662 ) in the two helices of the third intracellular loop alter the Ca 2+ sensitivity. The data suggested that the two helices in the third intracellular loop are essential for Ca 2+ -dependent activation .…”
Section: Ca 2 + and Voltage Dependence Of Tmem16amentioning
confidence: 99%